I stroll through places like I traverse folds in books (Palíndromo, 2024)
Is it possible to read an art exhibition like a publication? Can one walk through a book as through an exhibition space? Through the description and narration of a tour of an exhibition paralleled with the presentation of the spatiality of an illustrated book, we investigate the interrelation between the printed publication as an exhibition and the exhibition space as a publication. We also observe artworks produced in recent decades and the tension between the body of the book and the physical exhibition space, thus pointing towards the understanding that an art exhibition can traverse the reading experience, much like a publication.
Keywords: body of the book; expography; spatiality; illustrated book